2018
DOI: 10.1039/c8ra04936j
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of AgNWs@PDA@AgNPs core–shell nanocobs based on a mussel-inspired polydopamine for highly sensitive SERS detection

Abstract: An effective strategy was developed to controllably synthesize a series of AgNWs@PDA@AgNP core–shell nanocobs based on a mussel-inspired polydopamine and achieve highly sensitive SERS detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…When comparing the EDS peaks of the CS@PDA@AgNPs swabs with the original CS and CS@PDA swabs, an obvious peak of silver element emerged and demonstrated a significant intensity, which suggested that a mass of AgNPs were formed on the surface of the CS@PDA@AgNPs swabs. At the same time, four characteristic diffraction peaks at 2θ = 37.86°, 44.12°, 64.28°and 77.20° clearly emerged in the XRD spectrum of the CS@PDA@AgNPs swabs (Figure S2), corresponding to the (110), (200), (220) and (311) planes of the cubic silver crystal (JCPDS No.83-0718) [27,38]. From all of the above analyses, a controllable density of AgNPs was successfully in-situ grown on the surface of the CS@PDA@AgNPs swabs, based on mussel-inspired PDA surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When comparing the EDS peaks of the CS@PDA@AgNPs swabs with the original CS and CS@PDA swabs, an obvious peak of silver element emerged and demonstrated a significant intensity, which suggested that a mass of AgNPs were formed on the surface of the CS@PDA@AgNPs swabs. At the same time, four characteristic diffraction peaks at 2θ = 37.86°, 44.12°, 64.28°and 77.20° clearly emerged in the XRD spectrum of the CS@PDA@AgNPs swabs (Figure S2), corresponding to the (110), (200), (220) and (311) planes of the cubic silver crystal (JCPDS No.83-0718) [27,38]. From all of the above analyses, a controllable density of AgNPs was successfully in-situ grown on the surface of the CS@PDA@AgNPs swabs, based on mussel-inspired PDA surface chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, from the high-resolution Ag3d spectrum (Figure 3b), the binding energies for Ag 3d 5/2 and Ag 3d 3/2 were verified at 368.2 and 374.2 eV, respectively, and the approximate 6 eV splitting of the 3d doublet owing to the spin-orbit coupling further identified a single zero valence silver-element existence on the surface of the CS@PDA@AgNPs swabs [33]. Furthermore, the high-resolution C1s spectrum of the CS@PDA@AgNPs swabs was curved by four distinct peaks displayed at 289.05 eV, 288.15 eV, 286.5 eV and 284.8 eV (Figure 3c), which were attributed to the existence of carbonyl groups (C=O), the C–O groups, the C–N groups and saturated C–C bonding, respectively [27]. From Figure 3d, compared to the original cotton swab, the nitrogen peaks increased on the CS@PDA surface due to a functional PDA layer formation via DA self-polymerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the original fabric, a new N1s peaks can be detected for PDA/PET fabric (Figure 7b), which is attributed to the self-polymerization of PDA layer on the surface. Except for C1s, O1s, and N1s peaks, an extra Ag3d peak can be detected for Ag/PDA/PET fabric, indicating the presence of AgNPs on the surface of PET fabric (Figure 7c) [26]. For Cu/Ag/PDA/PET fabric (Figure 7d), the Cu 2p peaks have their major component at 932.6 eV (Cu 2p 3/2 ) together with a satellite peak centered at 952.5 eV (Cu 2p 1/2 ), which corresponds to metallic Cu [27].The strong signal of Cu 2p peak confirms the presence of Cu NPs on the surface of fabrics.…”
Section: Elemental Analysismentioning
confidence: 99%
“…Moreover, polydopamine (PDA) possesses strong complexation with metallic cations and reduces them spontaneously in-situ into metallic nanostructures by oxidizing catechols into the corresponding quinine groups [22,23,24,25]. As a result, PDA could serve as a versatile molecule platform to generate uniform silver nanoparticles (AgNPs) with desirable morphology and coverage density on NW fabrics, which provides a promising opportunity to fabricate a flexible SERS substrate for trace carbaryl pesticide detection [26,27,28].…”
Section: Introductionmentioning
confidence: 99%